KINERJA PEGAWAI DALAM PELAYANAN PUBLIK DI UPTD LABORATORIUM & PERALATAN DINAS BINA MARGA DAN PENGAIRAN KOTA SAMARINDA - Viky Hidayat (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The result show that employee’s performance at UPTD Laboratory and equipment of Bina Marga & Pengairan Samarinda in public service was implemented in work result both quantity and quality based on the work plan. It was also supported by a positive work behavior in doing the duty due to a condusive work environtment. Employee’s competency also becomes the important thing in public service it was gained from training and work experiences.